Bulk acoustic wave resonance characteristic modified by reducing the defects in ZnO-based solidly mounted resonators. (January 2022) - Ma, Lei; Zhang, Bo; Guo, Xin; Wang, Peng; Liu, Qingfang; Zheng, Kun; Li, Xiling; Wang, Jianbo
Abstract: The c -axis zinc oxide (ZnO) multi-layered films and ZnO-based solidly mounted resonators (SMR) based on high-resistivity silicon substrates have been fabricated by using the combination of sputtering and photolithography with the absence of oxygen and heating. Subsequent annealing procedure was performed to improve the quality of ZnO films and devices. The X-ray diffraction (XRD) measurements reveal that all ZnO films are well crystallized and highly textured, the grain size gradually increases from 18.2 to 20.5 nm with the increasing of annealing temperature ( T ann ). The X-ray photoelectron spectrometer (XPS) results indicate that the high concentration oxygen defects of as-deposited ZnO films can be reduced through increasing T ann . By comparing the measured electrical properties of the devices before and after various T ann annealing, it was found that the annealing treatment can be used to improve the resonance characteristics, the relative change in return loss (S11 ) increased from 0 to 0.72 dB and then decreased to 0.07 dB as T ann increases from room temperature to 700 °C. In addition, S11 relative change can also be enhanced from 0.29 to 0.67 by decreasing the effective working area of the devices from 100 × 160 μm 2 to 100 × 50 μm 2 .